Oral Microbiota: Microbial Biomarkers of Metabolic Syndrome Independent of Host Genetic Factors - Si, Jiyeon; Lee, Cheonghoon; Ko, GwangPyo (Frontiers in Cellular and Infection Microbiology, 2017)
The oral microbiota plays a critical role in both local and systemic inflammation. Metabolic syndrome (MetS) is characterized by low-grade inflammation, and many studies have been conducted on the gut microbiota from stool specimens. However, the etiological role of the oral microbiota in the development of MetS is unclear. In this study, we analyzed the oral and gut microbiome from 228 subgingival plaque and fecal samples from a Korean twin-family cohort with and without MetS. Significant differences in microbial diversity and composition were observed in both anatomical niches. However, a host genetic effect on the oral microbiota was not observed. A co-occurrence network analysis showed distinct microbiota clusters that were dependent on the MetS status. A comprehensive analysis of the oral microbiome identified Granulicatella and Neisseria as bacteria enriched in subjects with MetS and Peptococcus as bacteria abundant in healthy controls. Validation of the identified oral bacteria by quantitative PCR (qPCR) showed that healthy controls possessed significantly lower levels of G. adiacens (p = 0.023) and a higher ratio of Peptococcus to Granulicatella (p < 0.05) than MetS subjects. Our results support that local oral microbiota can be associated with systemic disorders. The microbial biomarkers identified in this study would aid in determination of which individuals develop chronic diseases from their MetS and contribute to strategic disease management.